THE EFFECT OF BREATHING RETRAINING PROGRAM ON LUNG FUNCTION FOLLOWING EXERCISE INDUCED DYSPNEA IN OBESE INDIVIDUALS - Pawar, Pournima Ajinkya; G. Varadharajulu (International Journal of Psychosocial Rehabilitation, 2020)
Obesity imposes additional stress to ventilation during exercise as a direct result of the increased body mass requiring greater metabolic energy exchange and secondary functional impairment as a result of altered pulmonary function. 1)To study the pulmonary function following exercise induced dyspnea. 2)To study the endurance after breathing retraining in obese individuals. Experimental study Research design with 33 subjects were included in this study with the help of convenience sampling who were diagnosed as Obese on the basis of their Body Mass Index (BMI) is more than 23 and age between 20-60 years. Informed consent was taken from patients who were participated in this study. They were informed about the study and basic knowledge of the effect of obesity on lung function was been given and the use of breathing retraining was highlighted. Pre- assessment such as pulmonary function testing immediately following shuttle walk test was done. And initially resistance applied for Inspiratory Muscle Training readings was been noted. The value of Forced Vital Capacity was noted in Pulmonary Function Testing. The distance covered in Shuttle Walk Test was been noted in meters, the Resistance applied for Inspiratory Muscle Training was been noted by Inspiratory Muscle Training device. This all patients were treated with breathing retraining. Mean of pre-intervention values of distance covered in shuttle walk test was 343.33 with SD 82.336 and mean of post-intervention values of distance covered in shuttle walk test was 416.96 with SD 103.21. Pre-intervention and post-intervention values were compared by applying paired ‘t’ test and it shows there is extremely significant difference in distance covered in Shuttle Walk Test. Based on the result and interpretation the present study shows that Breathing retraining program helps to improve lung function and inspiratory muscle strength in obese individuals.